A study of sea and land breeze over Goa - PRASAD, M.C.; PRADHAN , S. K.; KISHAN, DAYA (MAUSAM, 1977)
A statistical analysis of sea and land breeze has been made for Goa. Various aspects, such as, average time of onset, duration, direction at the time of onset and the associated changes in temperature and relative humidity have been studied and the results compared with that of Santacruz. The physical processes taking place have also been discussed. The main-characteristic features are that (i) weaker sea breeze circulation develops over Goa as compared to that over Santacruz, (ii) the surface temperature often continuous to rise and relative humidity often decrease even after setting in of sea breeze and iii) the maximum strength of sea. breeze is at 0.3 km and sharply falls by 0.9 km.